COMPARATIVE PARAMETRIC NUMERICAL SIMULATIONS OF MATERIALS USED AS LINERS IN THE EXPLOSIVELY FORMED PROJECTILES (EFPs) - Hussain, G.; Sanaullah, K. (The Nucleus, 2020)
A conventional shaped charge comprises a conical metal liner projecting a hyper velocity jet of metal that is able to penetrate to great depths into steel armour. However, misalignment problems exist in tandem with jet break up and spewing particles that greatly diminish its penetration power. An EFP, on the other hand, has a liner in the shape of a geometrical recess. The force of the blast molds the liner into a number of configurations, depending on the geometry and the explosive detonation characteristics. This paper presents comparative parametric numerical simulations of materials used as liners in the explosively formed projectiles EFPs. Numerical simulations are carried out using AUTODYN 2D hydrocode to study effects of liner’s materials on the shape, velocity, traveled distance, time, pressure, internal energy, temperature, yield stress, divergence or stability, density, compression, and length to diameter (L/D) ratio of EFPs. These parameters are estimated at the instants of maximum as well as at stable velocities. The parametric study reveals that aluminum has maximum velocity in shortest time among the liner materials. From this reason, it was concluded effective standoff was greater for aluminum than more denser metals. Maximum velocity and traveled distance of Tantalum EFP is found to be minimum which may be due to low thermal softening exponent and larger hardening exponent. The simulated yield stress and pressure developed in the Fe EFP reaches at maximum. The L/D ratio for Copper is found to be maximum which supports maximum penetration. From the stability point of view, 1006 MS is found to be the most reliable liner material due to minimum divergence. Generally all liner materials have similar effects of all parameters like pressure, internal energy, temperature, yield stress, divergence or stability, density, compression at the instants of maximum as well as at stable velocities except L/D ratio of EFPs. At the instant of maximum velocity, L/D ratio of Ta and AL EFPs have minimum and maximum L/D ratio respectively whereas Fe and Cu EFPs have minimum and maximum L/D ratio respectively. The velocity attenuation laws for liner materials from maximum to stable velocities are determined and plotted. The EFPs observed at maximum velocities are profilic except tantalum which shows a straight profile one due to higher density. The velocity attenuation laws show material for which maximum and stabilized velocity come earlier than other materials whereas tantalum is the liner’s material for which maximum and stabilized velocity take more time than other materials due to lower and higher densities respectively.